Understanding the Compositional Effects of SAFs on Combustion Intermediates - Mehl, M.; Pelucchi, M.; Osswald, P. (Frontiers in Energy Research, 2022)
This work analyses, experimentally and numerically, the combustion behavior of three aviation fuels: a standard Jet A-1, a high aromatic content fuel, and an isoparaffinic Alcohol to Jet (ATJ) fuel. The goal is to demonstrate the ability of a chemical kinetic model to capture the chemistry underlying the combustion behavior of a wide range of jet fuels, starting from compositional information. Real fuels containing up to hundreds of components are modeled as surrogates containing less than 10 components, which represent the chemical functionalities of the real fuel. By using an in-house numerical optimizer, the fuel components and their relative quantities are selected, and a semi-detailed kinetic model (containing about 450 species) is used to simulate the formation of the main oxidation products and reaction intermediates. Calculations are compared with species profiles measured in a laminar flow reactor to validate the model and provide insights into the reactivity of the fuels. Finally, starting from the results, general observations on the strengths and limits of the approach are provided, highlighting areas where further investigations are required.